2015
DOI: 10.1002/anie.201506045
|View full text |Cite
|
Sign up to set email alerts
|

Shaped Ceria Nanocrystals Catalyze Efficient and Selective Para‐Hydrogen‐Enhanced Polarization

Abstract: Intense para-hydrogen-enhanced NMR signals are observed in the hydrogenation of propene and propyne over ceria nanocubes, nano-octahedra, and nanorods. The well-defined ceria shapes, synthesized by a hydrothermal method, expose different crystalline facets with various oxygen vacancy densities, which are known to play a role in hydrogenation and oxidation catalysis. While the catalytic activity of the hydrogenation of propene over ceria is strongly facet-dependent, the pairwise selectivity is low (2.4% at 375 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 49 publications
3
66
0
Order By: Relevance
“…PHIP is a simple and robust method offering high polarization rates using relatively inexpensive instrumentation. The ease of separation of the hyperpolarized product from the polarizing agent is a key advantage of PHIP by heterogeneous catalysis . However, hyperpolarization levels afforded by supported metals and metal‐oxide catalysts have up to now been limited to only a few percent owing to the low pairwise selectivity of hydrogenation on metal surfaces.…”
Section: Figurementioning
confidence: 98%
See 3 more Smart Citations
“…PHIP is a simple and robust method offering high polarization rates using relatively inexpensive instrumentation. The ease of separation of the hyperpolarized product from the polarizing agent is a key advantage of PHIP by heterogeneous catalysis . However, hyperpolarization levels afforded by supported metals and metal‐oxide catalysts have up to now been limited to only a few percent owing to the low pairwise selectivity of hydrogenation on metal surfaces.…”
Section: Figurementioning
confidence: 98%
“…The activation barrier for this path is estimated at approximately 3 eV (calculated for acetylene) . Our previous study of propene (PE) hydrogenation showed that stepwise addition yields a facet‐independent 2–3 % pairwise selectivity over CeO 2 . Given that the lowest energy transition state for PY hydrogenation is one that promotes purely random addition, it follows that any NMR signal enhancement that might be observed in the PHIP spectrum must originate from either stepwise addition or concerted addition via the four‐membered‐ring transition state.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…However, the contributions of pairwise hydrogen addition with such catalysts were comparable to those for supported metal catalysts. In 2015 and 2016 Bowers and co‐workers studied the hydrogenation reactions of propene and propyne over CeO 2 nanocrystals of different morphologies (nanocubes, nano‐octahedra, and nanorods) . In the hydrogenation of propene, the percentage of pairwise hydrogen addition was 2.4 % with all of the catalysts, that is, there was no observed dependence on the shape of the nanocrystals.…”
Section: Heterogeneous Phipmentioning
confidence: 99%